Theoretical aspects of the relation between unemployment and vacancies - Wolfgang Franz; Karin Siebeck (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper is devoted to a theoretical analysis of the Beveridge curve, i. e. , the relation between unemployment and vacancies. Most empirical studies of the u - v curve for various countries find an outward shift thus indicating higher structural unemployment due to increased maladjustments on the labor market. The theory consists of three elements: the search process seen from both the employer's and the unemployed seeker's viewpoint and the matching technology governing the labor market. Major explanatory variables of possible shifts of the u - v curve are variables which determine the contact and contract probability, respectively, such as unemployment benefits, long-term unemployment, minimum hiring standards set by the firm, costs of regional mobility, training costs, turnover rate, perceived wage distribution. Many of these variables, however, have an ambiguous effect on the location of the Beveridge curve thus rendering this relationship a less straightforward tool to analyse structural unemployment and to draw policy implications to combat this type of joblessness.
Keywords: 330